Análise tecnológica e sócio-econômica do cultivo de moluscos bivalves em sistema familiar na baía da Ilha Grande, Angra dos Reis, RJ - Moschen, Fernando Vitor de Abreu [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Mariculture started as an activity among traditional fishermen families of Ilha Grande bay in 1996 through the Sustainable Development Project. This project, executed by the City council of Angra dos Reis, consisted of the installation of 20 marine farms. The species cultivated were the mussel Perna perna and the scallop Nodipecten nodosus, native species in the region with excellent potential with regards to zoo-technical performance and market-value. This study attempts to describe the state-of-the-art of shellfish culture in the region, through a socioeconomical survey, identifying production technologies of mussels and scallops being used by each producer. With the information and data gathered, it was possible to make an economical analysis of mussel and scallop culture in the region. Three culture configurations were analyzed: System A - composed of 4 long-lines, with production capacity of 3.030 of shell-on mussels and 7.500 units of scallops. System B - composed of 6 long-lines, with production capacity of 4.545 kg of shell-on mussel and 11.250 units of scallop. System C - composed of 18 long-lines with production capacity of 15.150 kg of mussels and 30.000 units of scallops. System A showed to be economically unfeasible after payment of local taxes (ICMS) upon marketed products. Nonetheless, this system showed feasibility if the taxes weren't applied. Systems B and C showed economically feasibility independently of the payment of taxes. The monthly gains varied between R$888,03 and R$3.799,57 according to the system.

A maricultura realizada junto às famílias tradicionais de pescadores artesanais da Baía da Ilha Grande foi introduzida no ano de 1996, pelo Projeto de Desenvolvimento Sustentável da Baía da Ilha Grande, executado pela Prefeitura Municipal de Angra dos Reis. Foram instaladas 20 fazendas marinhas que cultivam o mexilhão Perna perna e a vieira Nodipecten nodosus, espécies nativas que possuem grande potencial, tanto zootécnico como de mercado. Neste estudo buscou-se descrever o estado da arte, as tecnologias de cutivo e ações voltadas para a malacocultura da região, realizando-se um diagnóstico tecnológico e sócioeconômico dos maricultores familiares da Baía da Ilha Grande e identificando as tecnologias de produção de mexilhões e vieiras utilizadas pelos produtores. Com o conjunto de informações coletadas foi possível realizar uma análise econômica do cultivo de mexilhões e vieiras na região. Foram analisados três sistemas de cultivos chamados de Sistema A (4 long-lines, com capacidade para produção de 3.030 kg de mexilhões e 7500 unidades de vieiras), B (6 long-lines, com produção de 4.545 kg de mexilhões e 11.250 unidades de vieiras) e C (18 long-lines, com produção de 15.150 kg de mexilhões e 30.000 unidades de vieiras. Os sistemas A se mostrou inviável economicamente quando se inclui nos custos a cobrança do ICMS sobre os produtos comercializados. Ao não se considerar a cobrança deste imposto, este sistema apresentou viabilidade econômica. Os sistemas B e C se mostraram viáveis economicamente independente da cobrança de imposto. A receita mensal obtida variou de R$ 888,03 (Sistema A) a R$ 3.799,57(Sistema C).
Keywords: Maricultura; Viabilidade economica; Mexilhão - Criação; Vieira (Molusco) - Criação; Trabalho familiar; Mussels